Elastic modulus of tetrakaidecahedron open-cell cellular materials. (December 2015) - Zhang, L. G.; Zhu, H.; Yuan, L.
Abstract : In order to investigate the influence of the microstructure of open cellular materials on its properties, numerical simulations were performed to the open-cell tetrakaidecahedron model with a circle-strut transitional–junction. By means of the finite elements method, the influence of microstructure and relative density on elastic modulus is obtained. Results show that circle-strut radius and transitional–junction curvature radius are the primary factors of the relative density increment; influence of the non-linearity of relative density on relative elastic modulus is similar to that of the circle-strut radius on relative elastic modulus, both are obviously greater than that of the transitional–junction curvature radius on relative elastic modulus. For low-density cellular materials, the solid materials added at the intersecting part of the circle-struts brings same influence on elastic modulus for the model, but for high-density cellular materials, the solid materials added at the intersecting part of the circle-struts has greater influence on elastic modulus.